An audit of life cycle energy analyses of buildings - Yung, Ping; Lam, K.; Yu, C. (Elsevier, 2013)
Life Cycle Energy Analyses of buildings provide useful information for achieving sustainability. However, care must be taken when interpreting previous studies because of different life cycle stages included. Other problems found include the use of different types of areas and quality of data. This paper presents an audited database of Life Cycle Energy Analyses of buildings. A Literature Based Discovery method has been adopted to analyze 38 research works consisting of 206 cases. The average initial embodied energy for offices is found to be 10.47 GJ/m2 and that of residential property is 4.10 GJ/m2. When the initial embodied energy is expressed as number of years of heating and cooling energy, the range is very wide. However, when it is expressed as number of years of operational energy, the results are consistent (7.8 years for offices and 7.5 years for residential buildings). It is expected that the audited information on the energy requirement of buildings will provide valuable information for designers and decision makers.